Back to Uluzzo – archaeological, palaeoenvironmental and chronological context of the Mid–Upper Palaeolithic sequence at Uluzzo C Rock Shelter (Apulia, southern Italy). (9th August 2021) - Spinapolice, E. E.; Zerboni, A.; Meyer, M. C.; Talamo, S.; Mariani, G. S.; Gliganic, L. A.; Buti, L.; Fusco, M.; Maiorano, M. P.; Silvestrini, S.; Sorrentino, R.; Vazzana, A.; et al.
ABSTRACT: The tempo and mode of Homo sapiens dispersal in Eurasia and the demise of Neanderthals has sparked debate about the dynamics of Neanderthal extinction and its relationship to the arrival of H. sapiens . In Italy, the so‐called 'Transition' from Neanderthals to H. sapiens is related to the Uluzzian technocomplex, i.e. the first archaeological evidence for modern human dispersal on the European continent. This paper illustrates the new chronology and stratigraphy of Uluzzo C, a rock shelter and Uluzzian key site located in the Uluzzo Bay in southern Italy, where excavations are ongoing, refining the cultural sequence known from previous excavations. Microstratigraphic investigation suggests that most of the deposit formed after dismantling of the vault of the rock shelter and due to wind input of loess deflated by the continental shelf. The occasional reactivation of the hydrology of the local karst system under more humid conditions further contributed to the formation of specific layers accumulating former Terra Rossa‐type soil fragments. Superposed on sedimentary processes, strong bioturbation and the mobilization and recrystallization of calcite have been detected. Optically stimulated luminescence (OSL) ages from Uluzzo C Rock Shelter are congruent with previously published radiocarbon ages obtained on shell beads and tephrachronology from adjacent sites preserving the Uluzzian technocomplex such as Grotta del Cavallo, confirming the onset for the Uluzzian in the area to ca. 39.2–42.0 ka. The OSL chronology from Uluzzo C also provides a terminus post quem for the end of the Mousterian in the region, constraining the disappearance of the Neanderthals in that part of Italy to ≥46 ± 4 ka.